2015
DOI: 10.1093/ejcts/ezv380
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis with thymic epithelial tumour: a retrospective analysis of a Japanese database

Abstract: We conclude that earlier stage, smaller size or Type B thymomas are more frequently associated with MG, and MG may have no impact on the overall survival of patients with thymoma. We suggest that postoperative survival time of the patients with MG and thymic epithelial tumours may be mainly affected by the tumours, not by MG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 24 publications
6
48
4
Order By: Relevance
“…In other reports, the median maximal diameter of usual thymomas was 57-68 mm, and our case series was 50 mm, which was smaller than usual thymomas. 10,12,13) However, these cases were greater than or equal to 40 mm. Pathologically, only one case had type AB, and the other eight had type B (Type B1:B2:B3 = 4:3:1 cases).…”
Section: Commentmentioning
confidence: 82%
See 2 more Smart Citations
“…In other reports, the median maximal diameter of usual thymomas was 57-68 mm, and our case series was 50 mm, which was smaller than usual thymomas. 10,12,13) However, these cases were greater than or equal to 40 mm. Pathologically, only one case had type AB, and the other eight had type B (Type B1:B2:B3 = 4:3:1 cases).…”
Section: Commentmentioning
confidence: 82%
“…Pathologically, only one case had type AB, and the other eight had type B (Type B1:B2:B3 = 4:3:1 cases). All thymomas with ring calcification had pathologically 10,12) In this literature, 80% had thymomas equal to or more advanced than stage II, which meant that they were frequently invasive thymomas. Calcifications were pathologically found in more than half of the thymomas of type B2 and B3, and found more frequently in invasive thymomas than in noninvasive thymomas.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent analysis of the retrospective Japanese database of TETs that included 598 TETs in patients with myasthenia gravis did not reveal any difference in 5-and 10-year overall or recurrence-free survival. 19 A recent multicenter study from Italy including 375 patients with thymoma showed a slight protective effect of the presence of myasthenia gravis on overall survival, although that was not confirmed in multivariate analysis. 20 These findings suggest that today the outcome of patients with thymoma and myasthenia gravis is at least as good as the outcome of patients with thymoma without myasthenia gravis.…”
Section: Evolution Of the Histomorphologic Classification Of Thymic Ementioning
confidence: 94%
“…Up to 25% of thymoma patients will have clinically overt MG and an additional 25% of clinically asymptomatic thymoma patients will have circulating anti-acetylcholinesterase receptor (anti-Ach-R) autoantibodies. Conversely, in 5-15% of the patients with MG, preoperative work up eventually demonstrates an unsuspected thymoma (18,19).Thymectomy in MG patients may lead to long-term complete long-term remission (35-40% of patients), or to clinical improvement, i.e., discontinuation of steroids, less need for resorting to immunosuppressive therapy, lower incidence of myasthenic crisis or symptom improvement in another 30-45% (12,19). Complete removal of the thymus gland and anterior mediastinal fat from neck to diaphragm and phrenic-to-phrenic nerve (so called maximal thymectomy) is required, as microscopic islets of functional thymic tissue can be found throughout the anterior mediastinal fat in over 20% of the patients.…”
mentioning
confidence: 99%